“Saberes ancestrales en la producción agrícola de los campesinos del cantón Vinces, Provincia de Los Ríos” - Morán Nivela, Kleiner Fernando (2018)
SUMMARY ANCESTRAL KNOWLEDGE IN THE AGRICULTURAL PRODUCTION OF THE PEASANTS OF THE CANTON VINCES, PROVINCE OF LOS RIOS AUTHOR: Kleiner Fernando Morán Nivela TUTOR: Ing. Agr. Ricardo Chávez Betancourt, MsC. In agricultural production the use of ancestral knowledge has been losing space in the daily of the farmer, being replaced by technological practices that are applied in the crops; the use of machinery, seed selection, chemical products for pest control, disease and nutrition of our plantations. Therefore, this ancestral knowledge that has been inherited by generations disappears in time, thus losing the ancestral identification that identifies each community. The work was directed to farmers in the rural sector of the Vinces city, with the help of the interview made it is determined that the agricultural activity of the farmers of the city are more inclined to the production of maize, cocoa and banana, in lands under 5 ha. In sowing the use of hand tools such as small or stakes are very common; taking into account always the ideal months for the planting of each crop, and for maize the management of the lunar cycle for their respective sowing is an ancestral method very common for farmers. For the control of pests and diseases the use of chemicals predominates, referring to the fact the effect of these products is more vertiginous.